Measures and determinants of productivity growth in the South African manufacturing sector - Wright, Anthony John (Rhodes University, Faculty of Commerce, Department of Economics, 1994)
The neoclassical "sources-of-growth" approach is applied to derive total factor productivity (TFP) growth measures for manufacturing industries in South Africa. Although South Africa's recorded industrial TFP growth measures have been persistently low in absolute terms, this performance is not significantly worse than the industrial TFP growth performance of other developing countries. In some periods there is evidence of a significant variability in TFP performance across industries. The measures also indicate that TFP growth has worsened in the 1980s, particularly in the intermediate-capital intensive and labour intensive industries. However, there are various problems with interpreting neoclassical TFP growth measures as indicators of production efficiency. In fact, as TFP growth is derived as a residual, it may measure many factors besides production efficiency. Alternative growth theories are used to assess the fundamental determinants of productivity growth. These provide a more plausible conceptualisation of the process by which productivity growth is generated than the neoclassical growth theory does. However, this analysis also provides little empirical evidence of which underlying factors have had the most influence on productivity growth in South African manufacturing. Hence, the relative importance of possible candidates can only really be assessed qualitatively and on the basis of micro evidence. However, these assessments, and the assumptions underlying the postulated causal connections (between the identified factors and productivity growth), have a major impact on policy design. In this respect, on the basis of the framework provided by the evolutionary and other recent growth theories, various policy implications are drawn, and these are contrasted with the policy proposals of other South African analysts. This thesis concludes that policies need to be designed with the central objective of enhancing the technological capabilities of South African firms. Trade policies will not be sufficient for achieving this objective. Education and training policies, technology, competition and labour market policies are also crucial. However, since the fundamental causes of productivity growth remain somewhat of a mystery, there is a need to be sceptical of simple policy prescriptions. In this respect, this thesis is highly critical of the World Bank's position that productivity gains will be reaped from the exposure of firms to international competition that trade liberalisation policies entail.
Keywords: Industrial productivity -- South Africa